2021
DOI: 10.1124/dmd.121.000415
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X Receptor and the Gut-Liver Axis: A Recent Update

Abstract: It is well-known that the pregnane X receptor (PXR/Nr1i2) is a critical xenobiotic-sensing nuclear receptor enriched in liver and intestine and is responsible for drug-drug interactions (DDI), due to their versatile ligand binding domain (LBD) and target genes involved in xenobiotic biotransformation. PXR can be modulated by various xenobiotics including pharmaceuticals, nutraceuticals, dietary factors, and environmental chemicals. Microbial metabolites such as certain secondary bile acids (BAs) and the trypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 221 publications
1
19
0
Order By: Relevance
“…Moreover, IPA acts as a ligand of the aryl hydrocarbon receptor (AhR) present in colonic epithelial cells, activation of which is associated with anti-inflammatory and anticancer effects [119] Interestingly, it has been observed that in patients suffering from colitis serum, IPA concentration decreases significantly [28]. Apart from being an AhR ligand, IPA can also produce its biological action by activating the pregnane X receptor (PXR) present in colonic, liver endothelial and muscle cells [23,119,120]. Complex laboratory techniques allow testing the function of GBB by measuring its permeability to specific substances, including Fluorescein Isothiocyanate-Dextran (FITC-Dextran).…”
Section: Ipa Improves Gut-blood Barrier Functionmentioning
confidence: 99%
“…Moreover, IPA acts as a ligand of the aryl hydrocarbon receptor (AhR) present in colonic epithelial cells, activation of which is associated with anti-inflammatory and anticancer effects [119] Interestingly, it has been observed that in patients suffering from colitis serum, IPA concentration decreases significantly [28]. Apart from being an AhR ligand, IPA can also produce its biological action by activating the pregnane X receptor (PXR) present in colonic, liver endothelial and muscle cells [23,119,120]. Complex laboratory techniques allow testing the function of GBB by measuring its permeability to specific substances, including Fluorescein Isothiocyanate-Dextran (FITC-Dextran).…”
Section: Ipa Improves Gut-blood Barrier Functionmentioning
confidence: 99%
“…After all, the liver and small intestine are PXR-enriched sites. 20,30,49 In summary, IPA has played a BBB protective role in the neonatal rat model of HI brain injury. IPA can attenuate inflammation by inhibiting NF-κB signaling.…”
Section: ■ Resultsmentioning
confidence: 91%
“…IPA is an endogenous activator that can activate the Pregnane X receptor (NR1I2, PXR). 20,21 Moreover, PXR has been approved to play an anti-inflammatory role by inhibiting the actions of the NF-κB signaling pathway 22−24 and hypoxia can potently inhibit the expression of PXR. 25 Therefore, we hypothesize that PXR is involved in the protective effect of IPA on BBB.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations